Successful endoscopic duodenal stent placement for afferent loop obstruction following Billroth II gastrectomy: a case report - Ye, Shanliang; Peng, Yong; Zhuang, Wenhang; Mo, Zhiqiang (Frontiers in Oncology, 2025)
BackgroundAfferent loop obstruction (ALO) is an uncommon but potentially life-threatening complication following Billroth II gastrectomy, with an estimated incidence of around 1%. It often presents with nonspecific symptoms such as postprandial vomiting and jaundice, making timely diagnosis and effective treatment crucial. Minimally invasive endoscopic techniques have emerged as promising alternatives to surgery.Case presentationWe report the case of a 63-year-old woman with a history of Billroth II gastrectomy for gastric cancer who presented with progressive jaundice, nausea, and vomiting. Imaging revealed significant duodenal wall thickening consistent with ALO. Conventional endoscopic attempts to traverse the obstructed segment failed due to severe luminal narrowing and tortuosity. Under combined endoscopic and interventional radiologic guidance, a duodenal self-expanding metal stent was successfully deployed across the stricture, resulting in immediate symptom relief and biochemical improvement.ConclusionInterventional-guided endoscopic stent placement is a safe, effective, and minimally invasive approach for managing malignant or benign ALO in post-gastrectomy patients. This hybrid technique may be particularly valuable in anatomically complex or surgically high-risk cases.